Potential therapeutic uses of interleukin 1 receptor antagonists in human diseases. Issue 11 (1st November 2002) - Hallegua, D S; Weisman, M H
Abstract : Objective: To review publications relating to the blocking of interleukin 1 (IL1) as a strategy for treating human disease, ranging from rheumatoid arthritis (RA) to Alzheimer's disease. Methods: The National Library of Medicine's PubMed database was searched for articles about pharmaceutical agents that reduce the biological actions of IL1. Results: Fish oils and corticosteroids were identified as non-selective pharmacological interventions that reduce the activity of IL1, whereas a recombinant human IL1 receptor antagonist (anakinra) and a soluble recombinant type I IL1 receptor act selectively. To date, anakinra is the only selective intervention that has been shown in controlled clinical trials to be effective and well tolerated in the treatment of a specific human disorder, RA. In controlled clinical trials, anakinra provided significant clinical improvement and slowed radiographic disease progression in patients with active RA. Moreover, addition of anakinra to existing methotrexate treatment significantly reduced signs and symptoms of active disease. Conclusions: The clinical use of anakinra has been demonstrated in the management of RA, but blocking of IL1 in other human disorders, as well as the safety of the use of these blocking agents in chronic diseases, still needs to be defined by controlled clinical investigations.